المجاز وتقديمه للطلبة الناطقين بغير العربية: دراسة وصفية تحليلية - الخدام، غدير عبدالمجيد عبدالله; الفاعوري، عوني صبحي (جامعة السلطان قابوس - كلية الآداب والعلوم الاجتماعية, 2020)
هدفت هذه الدراسة إلى بحث المجاز وضبطه عند تقديمه للطلبة الناطقين بغير العربية والتوصل إلى طرق مقترحة لتقديم المجاز لهم، بحيث يقدم هذا الدرس البلاغي الجامد بأبسط الطرق دون إخلال أو تقصير انسجاما مع حاجات الطلبة وتوجهاتهم في الدراسة. وقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي. وقد جاءت الدراسة في ثلاثة مباحث، تناول المبحث الأول معنى المجاز ونشأته وتقسيماته. وفي المبحث الثاني، تناول الباحثان المجاز في أربعة من كتب تعليم العربية للناطقين بغيرها، ثلاثة منها في الغرض العام وهي كتاب )الكتاب) في تعلم العربية، كتاب العربية بين يديك، كتاب العربية للناطقين بغيرها )الجامعة الأردنية(، وكتاب Advanced Media Arabic في الغرض الإعلامي الخاص، وذلك في محاولة لرصد طرق تقديم المجاز فيها، واستنتاج أهم التمارين التي تساعد في تقديم المجاز وعرضه للطلبة الناطقين بغير العربية. وتناول المبحث الثالث طرائق مقترحة في تقديم المجاز للطلبة الناطقين بغير العربية استنادا إلى ما توصلت إليه الدراسة من استنتاجات في المبحث الثاني. وقد خلصت الدراسة إلى مجموعة من النتائج والتوصيات وردت في آخر الدراسة.
The study aimed to study and adjust metaphor while introducing it to non-native speakers of Arabic, and to suggest new methods in order to introduce the static metaphor lessons to non-native students in the simplest ways without disruption or any cutting in harmony with the students’ needs and their orientations in studying. The study was based on the descriptive analytical method, in which the researchers studied metaphor from four books of teaching Arabic to non-native speakers; three of them were in the general purpose and these books were: Al-Kitaab, Arabic between your hands, and Arabic for non-native speaker’s book. The fourth book was advanced media Arabic book, which was in the diplomatic special purpose. The researchers used these books and tried to observe the introducing methods for metaphor in these books, also to conclude the most important exercises which will help in introducing metaphor to non-native speakers of Arabic. The results showed that representing metaphor lessons for foreign students in books and search orbit began from the linguistic meaning of metaphor which means commuting the direct meaning for some terms and expressions to another one. And there were not any specifications in dealing with metaphor as an independent metaphoric lesson, instead of that metaphor was merged in the readings and audios scripts or the ones that the student requested to write. All of that to deal with metaphor as one of the skills that the student acquired during his studying process without specification. Based on the previous results, this study advises to make a distinguish when it comes to introduce metaphor to the students, whether they are a native speakers or non-native ones or studying Arabic language for a special metaphoric purpose, as well as the study advises each of the author and the tutor to simplify the metaphoric tittles as much as they can; in which this simplifying will facilitate the learning process without being affected on the meaning. This study recommends to make more studying around the metaphoric topic in order to adjust the manifold types and to put them in a frame to make them easily to deal with also to represent them in more efficiency and active way.
Keywords: اللغة العربية -- الناطقين بغير العربية -- علم المجاز -- البلاغة العربية